Antiplasmodial Test of Tinospora crispa Stem Extract against Plasmodium falciparum 3D7 Strain In Vitro - Ihwan, Ihwan; Rifa'i, Muhaimin; Fitri, Loeki Enggar (Fakultas Kedokteran Universitas Brawijaya, 2014)
This study aimed to prove the existence of anti-plasmodial activity from Tinospora crispa (T. crispa) stem extracts and to determine the IC50 values as well as the best T. crispa stem extract concentration in inhibiting the growth of P. falciparum 3D7 strain in vitro. The degree of parasitemia was observed by counting the number of infected red blood cells in Giemsa stained blood films under a light microscope with a magnification of 1000x. The Plasmodium DNA concentration was measured using flow cytometryc with Propidium Iodide (PI) staining. Analysis of fourier transform infrared (FTIR) spectrophotometer showed that the methanol extracts of T. crispa stem contained tinocrisposide compound. From the quantitative test results of Thin Layer Chromatography (TLC), it was obtained 0,22 % alkaloids that might contain compounds of berberine and palmatine. One way ANOVA statistical analysis showed that the degree of parasitemia and the concentration parasite DNA of treatment group of dose of 2,0mg/ml was significantly lower compared to the control group after 48 hours (p=0,001) and 72 hours (p=0,001) of incubation. The T. crispastem methanol extract has anti-plasmodium activity, with IC50 values between 0,27 mg/ml and 0,29mg/ml, and the effective dose to inhibit the growth of P. falciparum 3D7 strain is 2,0 mg/ml with reducing parasitemia degree by 47,12% and 56,83% after 72 hours of incubation. From this study shown the methanol extract of T. crispastem was able to reduce the parasitemia degree of P. falciparum 3D7 strain in vitro and could to be a potential candidate for anti malarias.Keywords: Antiplasmodium, methanol extract, T. crispa, Plasmodium falciparum